2008
DOI: 10.20965/jdr.2008.p0334
|View full text |Cite
|
Sign up to set email alerts
|

Recent Peat Fire Activity in the Mega Rice Project Area, Central Kalimantan, Indonesia

Abstract: The original objective of theMega Rice Project (MRP) in CentralKalimantan, Indonesia – to convert onemillion hectares of tropical swamp forest to paddy fields – instead produced large areas of abandoned farmland with bare peat subject to frequent fires. To understand how peat fire occurrence is related to drought, we analyzed 1997 to 2007 United States Department Commerce National Oceanic and Atmospheric Administration (NOAA) hotspot data, sea surface temperature (SST) anomalies, and weather data. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 5 publications
3
33
0
1
Order By: Relevance
“…Our previous study (Putra et al 2008) showed that more than 90% of peat fires in Central Kalimantan from 1997 to 2007 occurred in the dry season.…”
Section: Fires and The Dr Y Season Occur Together In Allmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous study (Putra et al 2008) showed that more than 90% of peat fires in Central Kalimantan from 1997 to 2007 occurred in the dry season.…”
Section: Fires and The Dr Y Season Occur Together In Allmentioning
confidence: 98%
“…However, previous studies indicated that after 1997 forest and peat fires in Indonesia tend to occur ever y year in the dr y season (Dennis 1999, Adinugroho et al 2005, Murdiyarso and Aidaningsih 2006, Ministry of Forestry 2008, even in non El Niño years (Putra et al 2008). This change in fire incidence in Indonesia may be related to the rapid decrease in forest areas.…”
Section: Introductionmentioning
confidence: 99%
“…The objective was to convert one million hectares of tropical swamp forest to rice paddy fields and promote transmigration. This resulted in large-scale deforestation and peatland drainage mostly in the province of Central Kalimantan (Putra et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Major fire events occurred in Kalimantan in 1846, 1902, 1915, and 1972, all of which were El Niño Southern Oscillation (ENSO) years [8]. El Niño reduced precipitation drastically [9], which makes peatland more susceptible to fire due to lowered water table [10]. Local communities in East Kalimantan and South Sumatra have traditionally conducted slashing and burning in peat swamp forests along the river bank and forest edges to convert the forest to agricultural land ( [11] [12]).…”
Section: Introductionmentioning
confidence: 99%